Validation of non-exhaustive test to determine the aerobic capacity in swimming - Gobatto, C. A.; Gomes de Araujo, G.; Santhiago, V.; Papoti, M.; Manchado-Gobatto, F. B. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: Several methods of aerobic capacity evaluation have been applied to assess and prescribe the training sessions in swimming. However, most protocols either show exhaustive characteristics, triggering transitory stress period or several visits, influencing the session's organization. Thus, the purpose was to validate a double-bout exercise protocol for non-exhaustive aerobic capacity determination of swimmers.